Beyond Violence - Mahdi Tourage (International Institute of Islamic Thought, 2006)
This book contains six essays presented at an international conference entitled “Beyond Violence: Religious Sources of Social Transformation.” It brings together academic and activist Jews, Christians, and Muslims to explore the potential of each religious tradition as a source of peaceful social transformation. The book thus problematizes the assumption that violence is minimized by excluding religion from public life. The book appropriately opens with Charles Taylor’s (McGill University) paper, which draws heavily on the thoughts of French philosopher Rene Girard Violence and the Sacred (Baltimore: The Johns Hopkins University Press: 1979). Taylor explores the modes of transition of violence from purifying killing with metaphysical roots to political “categorical violence,” which makes ethnic cleansing possible. He gives a tripartite solution to violence: building ordered democratic polities that are likely to be less violent, spreading the benefits of such a society widely to prevent the formation of desperate excluded groups, and denouncing the self-righteous reconstitution of violence for revenge by those who have suffered. These first two solutions involve political and economic correctives at the governmental level, which may not hold true in the face of evidence. For example, violence could be caused by a most democratic polity that finds no incentive to spread its benefits, even to the most desperate of its own people. Taylor’s third solution, however, can resonate on a very personal level with many who, as a result of suffering, feel entitled to revenge. It is forgiveness, he argues, and a recognition of a common, flawed humanity that may suppress the madness of revenge and violent categorization (pp. 38-40) ...